User Experience with Spherical Layout - Martin Larrea; Dana Urribarri; Sergio Martig; Silvia Castro (CGVCVIP'09: Proceedings of the International Conference on Computer Graphics, Visualization, Computer Vision and Image Processing, 2009)
The 3D tree visualization faces multiples challenges: the selection of an appropriate layout and the use of proper interactions will help the information understanding. A good combination of these two elements (layout + interactions) will result in a visualization that effectively conveys the key features of a complex structure or system to a wide range of users and permits the analytical reasoning process. In previous work we have presented the Spherical layout; this layout allows the representation of larger information sets, at different levels of detail in a 3D environment. The goal of this work was centered in a user experience for this layout. We developed a file browser application based on the Spherical layout, called Brows.AR, and compared it with Windows File Browser. The results of this experience are shown in this paper.